Effect of strain rate on fractography texture descriptor of AA6063/(Si3N4)x/(Cu(NO3)2)y (x=12%, y = 2–6%)composite after multiple ECAP passes: second order statistical texture analysis conjunction with regression analysis - P. Sureshkumar; L. Ganesan; C. UmaRani; B. Stalin; C. Sasikumar; S Thanga Kasi Rajan; W. Borek (Journal of Materials Research and Technology, 2023)
The tensile strength of the ECAP processed composite of AA6063/(Si3N4)x/(Cu(NO3)2)y (x=12%, y=2-6%) at various strain rates from 0.0001 to 1s-1 with an increment of 10 was examined in relation to the seven-fracture image texture descriptor through void features such as void size and distribution. In order to measure the matrices of voids on the fracture surface created through the coalescence of void results to enhance the material hardening as strain rate increases, the second order statistical texture analysis has been used. With respect to the rising strain rate, it was observed that the composite fracture image feature parameter correlation, homogeneity improved by 6 %, and 20.74% for AA6063/12%Si3N4/6%Cu(NO3)2 after I passes as compared to AA6063/12% Si3N4 after III pass. The contrast was reduced by around 58.643% when reinforcement went from a single reinforcement of 12% Si3N4 with I Pass to a composite of two reinforcements (Si3N4, Cu(NO3)2) that had 6% Cu(NO3)2 with I Pass. After three passes on AA6063/12%Si3N4/2%Cu(NO3)2, the maximum entropy was seen due to the material's increased plastic deformation, which led to an uneven particle distribution. As strain rate and copper nitrate percentage grew from 0 to 6 percent, the tensile strength of the composite improved by 34.69%. To assess the importance of fracture image features in relation to tensile strength with respect to strain rate, a regression model was developed. In order to get information about the fracture studies from fractography, the contrast with varying strain rate was nevertheless the aspect, which had the greatest influence.